Updating the distribution of the genus Isoetes (Isoetaceae) in southern Spain(Córdoba, Andalusia) - Javier López-Tirado (Caldasia)
Isoetes belong to the Class Lycopodiopsida (lycophytes). The genus is generally underrepresented in collections due to a lack of diagnostic characteristics and inconspicuous appearance. The current dis-tribution of Isoetes within Córdoba province is provided in a 1 km2 grid from several sources: (i) her-baria sheets from COA, COFC, MGC, SEV, GDA, and GDAC, (ii) 107 new observations since 2012, and (iii) records from literature and databases. Nine herbaria sheets were correctly determined. The most frequent species was I. histrix, well represented in the northern half of the province. Isoetes durieui, I. longissima, and I. delilei were much less common. The present work aims to update the current distri-bution of this genus in Córdoba province (Spain), in which several species are classified as threatened.